THE EFFECTS OF PINUS MASSONIANA (PINE POLLEN) AS ADJUVANT THERAPY ON LEUKOCYTES, T LYMPHOCYTES, C-REACTIVE PROTEIN, AND D-DIMERS IN HOSPITALIZED COVID-19 PATIENTS - Prettysun Ang Melow; Handi Suyono; Maria Magdalena Ano Djoka; Agata Christi Palupi; Steven Hermantoputra; Anton Hariadi; Yudita Wulandari; Sri Purwaningsih (JURNAL WIDYA MEDIKA, 2022)
Introduction: SARS-CoV-2 infection has caused the Corona Virus Disease-19 (COVID-19) pandemic until present day. Pine pollen has been known and used as a medicine and has benefits for immunity. Aim: To determine the effects of Pinus massoniana (pine pollen) as an adjuvant on leukocytes count, T lymphocytes (CD4, CD8) count, plasma C-reactive protein level, plasma D-dimer level in hospitalized COVID-19 patients with moderate-severe clinical manifestation. Materials and Method: We used a double blind pretest-posttest control group design, with 2 groups, namely control (placebo) and treatment. The subjects were selected by simple random sampling, male and female patients aged 20-60 years. Peripheral blood samples were taken before and after treatment. Patients were given pine pollen or placebo 3 x 4 capsules (3 g / day) for 7 days. Data were analyzed by SPSS 23.0 t-test with significant value of p < 0.05. Results: The patients of treatment group were 16 people (13 male, 3 female), average age 46,25 years and control 13 people (10 male, 3 female), average age 47,92 years. The leukocytes count increased not significantly in the treatment group (p=0.499; 8.03%) while control increased significantly (p=0.027; 36.42%). The leukocytes count of control was 4,5 times greater than treatment group. The CD4 count increased significantly in the treatment group (p=0.004; 73.44%) and control (p=0.048; 28.97%), and the it was 2,5 times greater than control. The CD8 count increased significantly in the treatment group (p=0.005; 72.90%) and control (p=0.033; 34.66%), and it was 2,1 times greater than control. CRP levels were significantly reduced in the treatment group (p=0.001; 71.61%) and control (p=0.001; 78.13%). D-dimer levels decreased significantly in the treatment group (p=0.048), while the control increased but not significantly (p=0.200). The D-dimer level in the treatment group decreased by 37.93%, while the control increased by 43.70%. Conclusion: Further research is still needed to explore the effect of pine pollen on cellular immunity which in this case is T lymphocytes, especially CD4 and CD8, and hemostasis (coagulation) especially D-dimer. Pine pollen is beneficial for immune modulation in COVID-19 patients.